Legacy persistent organic pollutants including PBDEs in the trophic web of the Ross Sea (Antarctica). (October 2017) - Corsolini, Simonetta; Ademollo, Nicoletta; Martellini, Tania; Randazzo, Demetrio; Vacchi, Marino; Cincinelli, Alessandra
Abstract: The ecological features of the Ross Sea trophic web are peculiar and different from other polar food webs, with respect to the use of habitat and species interactions; due to its ecosystem integrity, it is the world's largest Marine Protected Area, established in 2016. Polar organisms are reported to bioaccumulate lipophilic contaminant, viz persistent organic pollutants (POPs). Legacy POPs and flame retardants (polybrominated diphenyl ethers, PBDEs) were studied in key species of the Ross Sea ( Euphausia superba, Pleuragramma antarctica ) and their predators ( Dissostichus mawsoni, Pygoscelis adeliae, Aptenodytes forsteri, Catharacta maccormicki, Leptonychotes weddellii ). Gaschromatography revealed the presence of PCBs, HCB, DDTs, PBDEs in most of the samples; HCHs, dieldrin, Eldrin, non- ortho PCBs, PCDDs, PCDFs were detected only in some species. The average ∑PBDEs was 0.19–1.35 pg/g wet wt in the key-species and one-two order of magnitude higher in the predators. Penguins and skuas from an area where a long-term field camp is located showed higher BDE concentrations. The ΣDDTs was higher in the Antarctic toothfish (20 ± 6.73 ng/g wet wt) and in the South Polar skua (5.911 ± 3.425 ng/g wet wt). The TEQs were evaluated and the highest concentration was found in the Weddell seal, due to PCB169, 1, 2, 3, 4, 7, 8-HxCDF, and 2, 3, 4, 6, 7, 8-HxCDF. There was no significant relationship between the trophic level and the POP concentrations. Although low concentrations, organisms of the Ross Sea trophic web should be further studied: lack of information on some ecotoxicological features and human impacts including global change may distress the ecosystem with unpredictable effects. Graphical abstract: Highlights: PBDEs were higher in Adèlie penguin and skua nesting around a long-term field camp. DDTs were 56% in toothfish, 59% in Weddell seal; PCBs were 52–98% in the other species. No significant relationship between trophic level and POP concentrations was found. Lipid content in the toothfish is high and affects the POP bioaccumulation. POPs in the food web of the Ross Sea were lower than those from other areas.